2008
DOI: 10.1002/ejic.200800548
|View full text |Cite
|
Sign up to set email alerts
|

Manganese(II) Trimeric Systems Derived from Pyridyldioximato Ligands: Synthesis, Crystal Structure, and Magnetic Characterization

Abstract: Three new manganese compounds have been obtained by reaction of the 2,6‐diacetylpyridine dioxime (dapdoH2) ligand with several MnII salts. By using a variety of manganese(II) carboxylates, three MnII derivatives with general formula [Mn3(RCOO)6(dapdoH2)2], where RCOO– = formate (1), acetate (2), and benzoate (3), were obtained. Structural analysis reveals chains of trinuclear units for 1 and isolated trinuclear molecules for 2. Compound 1 provides an example of a new topology for the [Mn3(RCOO)6(L)2] general f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
21
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 30 publications
2
21
0
Order By: Relevance
“…In the previous related reports, we note that although a dozen of compounds with similar bridges were characterized structurally and magnetically, no unambiguous correlations were found between the structural parameters (such as Mn-O bridge -Mn angles and the bond parameters of the syn-syn carboxyalte bridges) and the J values due to the complexity arising from the coexistence of mixed oxygen and carboxylate bridges, the presence of unpaired five electrons per Mn(II) and the effects of the terminal ligands. Compound 1 shows a relatively weaker interaction than the previous compounds which may be accounted for the longer Mn-O bridge distance (2.37 Å, 2.49 Å) and the Mn⋯Mn distance (3.69 Å, 3.76 Å) spanned by the mixed bridges than those (2.18-2.33 Å for Mn-O bridge and 3.43-3.69 Å for Mn⋯Mn distance) for the previous reported compounds [23][24][25][26][36][37][38][39].…”
mentioning
confidence: 78%
“…In the previous related reports, we note that although a dozen of compounds with similar bridges were characterized structurally and magnetically, no unambiguous correlations were found between the structural parameters (such as Mn-O bridge -Mn angles and the bond parameters of the syn-syn carboxyalte bridges) and the J values due to the complexity arising from the coexistence of mixed oxygen and carboxylate bridges, the presence of unpaired five electrons per Mn(II) and the effects of the terminal ligands. Compound 1 shows a relatively weaker interaction than the previous compounds which may be accounted for the longer Mn-O bridge distance (2.37 Å, 2.49 Å) and the Mn⋯Mn distance (3.69 Å, 3.76 Å) spanned by the mixed bridges than those (2.18-2.33 Å for Mn-O bridge and 3.43-3.69 Å for Mn⋯Mn distance) for the previous reported compounds [23][24][25][26][36][37][38][39].…”
mentioning
confidence: 78%
“…Crystal data for 1:C 48 H 42 Mn 3 N 12 O 12 , M w = 1143.76 gmol À1 ,t riclinic,space group P1 , a = 8.4873 (17), b = 11.710(2), c = 13.099 (3) , a = 98.891 (12), b = 104.418 (11), g = 104.768 (11) 8 8, V = 1185.7(4) 3 , Z = 1, m = 7.073 mm À1 , 1 calcd = 1.602 Mg m À3 , R 1 = 0.0456, wR 2 = 0.1131.…”
Section: Methodsmentioning
confidence: 99%
“…[9,7c] This anion is quite intriguing because of the presence of unquenched orbital angular momentum originating from first-order spinorbit coupling of the low-spin (LS) t 2g 4 Mn III ion, which endows it with significant single-ion anisotropy.T his anionic building block is ap romising candidate for both SMMs and SCMs,provided the chemistry can be controlled. [12] We postulated that the labile acetate bridging ligands could be replaced with [Mn(CN) 6 ] 3À anions,a nd that the chelating tptz ligands would serve to prevent the extension of the structure to atwo-dimensional layered motif (Scheme 1). [10] Theoretical studies based on this compound led to the prediction that al inear trinuclear molecule containing the Mn II ÀNCÀ Mn III ÀCNÀMn II unit should exhibit an SMM barrier height larger than 100 K, ah ypothesis that has yet to be tested.…”
mentioning
confidence: 99%
“…Crystal data for 1:C 48 H 42 Mn 3 N 12 O 12 , M w = 1143.76 gmol À1 ,t riclinic,space group P1 , a = 8.4873 (17), b = 11.710 (2), c = 13.099 (3) , a = 98.891 (12), b = 104.418 (11), g = 104.768(11)8 8, V = 1185.7(4) 3 , Z = 1, m = 7.073 mm À1 , 1 calcd = 1.602 Mg m À3 , R 1 = 0.0456, wR 2 = 0.1131.…”
Section: Methodsmentioning
confidence: 99%
“…We initiated this work by targeting the use of the centrosymmetric linear trinuclear compound [(tptz) 2 Mn II 3 (OAc) 6 ](1,tptz = 2,4,6-tri(2-pyridyl)-1,3,5-triazine), which contains two different environments for the Mn II ions. [12] We postulated that the labile acetate bridging ligands could be replaced with [Mn(CN) 6 ] 3À anions,a nd that the chelating tptz ligands would serve to prevent the extension of the structure to atwo-dimensional layered motif (Scheme 1). Indeed, slow diffusion of { [18-C-6 K} 3 [Mn(CN) 6 ] into 1 affords the unusual compound {[(tptz)Mn II (H 2 O)-Mn III (CN) 6 ] 2 Mn II (H 2 O) 2 } n ·4n MeOH·2n H 2 O( 2 )w ith at apelike chain structure.Magnetic studies revealed that 2 exhibits long-range magnetic ordering below 5.1 Kthat is due to both intra-and inter-chain antiferromagnetic couplings as well as SCM behavior at lower temperatures with an effective energy barrier of 40.5(7) K.…”
mentioning
confidence: 99%